Exposição pré-natal ao lipopolissacarídeo como modelo translacional de transtorno do espectro autista - Vieira, Fernando Vitor (2017)
Autistic Spectrum Disorder (ASD) is a psychiatric behavioral development disorder of unknown etiology that affects 1:88 children born, the ratio of boys to girls being 4:1. It is characterized by delay or absence of verbal communication, visual contact, social interaction, repetitive and/or stereotype movements among others. Detection usually occurs before 3 years of age and often detected at 6 months. Some lines of research attest that genetic, neurological, immunological factors, prenatal viral infections, food and environmental contaminants could be the cause of it. The present work proposes the animal experimentation as a model of ASD to understand the causes and consequences of prenatal infections in pregnant rats and consequence on offspring behavior. The proposed aims to mimic infections during gestation with the administration of lipopolysaccharide (LPS) extracted from the cell wall of gram-negative bacterial, injected intraperitoneally (i.p.) at doses of 100 μg/Kg at 9.5 or 500 μg/Kg in the gestation day 16 (GD9.5 and 16), or saline solution (SAL) 1ml/Kg i.p. and later behavioral analysis of the born pups. The data from the USV's, Homing, hole-board, elevated plus maze and play behavior tests show that of male offspring treated with LPS at a dose of 500 μg / kg in GD16 had autistic-like behavior, the same behavior was not observed in females. Likewise, male and female animals treated with LPS at the dose 100 μg/Kg in GD9.5 did not present difference in relation to the animals that received SAL.